Correlation between Instrumental Activities of Daily Living and Muscle Mass in Older Adults: Impact of Comorbidities - M. Lucía Fernández-Millones; Gianelli S. Curi-Vilchez; Jose F. Parodi; Fernando M. Runzer-Colmenares (Annals of Geriatric Medicine and Research)
Background There is evidence that sarcopenia and functionality are closely related. However, the association between geriatric syndromes, such as dependence, on instrumental activities and sarcopenia could be affected by the presence of certain comorbidities, such as overweight, obesity, diabetes, and chronic obstructive pulmonary disease (COPD). Therefore, the present study aimed to determine the association between instrumental activities of daily living and muscle mass in the elderly and evaluate the impact of certain comorbidities on this association. Methods This was a retrospective analytical observational study, including 1,897 patients. Muscle mass was measured with calf circumference, and instrumental activities were measured with the Lawton index. Results Among different parameters studies, a statistical correlation was found in a stratified regression analysis between the Lawton index score and muscle mass in patients who were overweight (p=0.001, β coefficient=0.08), obese (p=0.001, β coefficient=0.05), had diabetes (p=0.012, β coefficient=0.03), and had COPD (p=0.001, β coefficient=0.03). Conclusion The correlation between muscle mass and instrumental activities of daily living should be evaluated individually according to the needs of each participant and according to their comorbidities, promoting patient-centered geriatric medicine.